LITERATURE REVIEW: ANALYSIS OF THE INFLUENCE OF SOCIALINTERACTION ON STUDY OF STUDENTS SPECIAL NEEDS IN HIGH SCHOOLS - Mikra, Dini Pebrianti; Rahmatika, Helsa; Avichena, Avichena; Enjelly, Enjelly; Septiani, Freliana; Iksan, Mila Hidayatul (JPI (Jurnal Pendidikan Inklusi), 2024)
Education is considered a very important forum for children to achieve prosperity, including social. Education does not always go according to expectations, it can be said that national education in Indonesia has not all been fulfilled, onevway tovovercomevthe socialvproblems of childrenvwithvdisabilities isvinclusiveveducation. Thevaim ofvthis researchvis tovanalyze the influencevofvsocial interactionvon the learningvmotivationvofvstudents with special needs in high school. This research uses descriptive qualitative research using literature study as the research design. The conceptual and theoretical approach is carried out by referring to various sources such as scientific journals, the internet, and books. Descriptions and ideas from all sources are combined into one framework of thought. Based on the research results, students' learning motivation is influenced by the social interaction of peers. Any increase in socialvinteraction with peers will cause students to be more motivated to learn. Itvcanvbe concluded that the ability ofvchildren with special needs (ABK) to interact with other people is better influenced by social support. the good one. If ABK's social interactions are good, this can influence their motivation to learn. Keywords: childrenvwith specialvneeds (ABK), learning motivation, socialvinteraction.